(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper explores the landscape of fixed point theory by introducing two novel classes of contraction mappings: the (αs, νs,(Q, h)-F)-contraction and the (αs, ηs, νs,(Q, h)-F)-contraction, defined within the rich structure of triple-controlled S-metric type spaces. These mappings are constructed using a blend of αs- and ηs-admissibility, νs-subadmissibility, and a pair of upper-class functions (Q, h), integrated with Wardowski’s powerful F-contraction approach. Our results significantly extend the classical (αs F)-contraction framework by proving the existence and uniqueness of fixed points under these generalized settings. Furthermore, we derive meaningful corollaries by specifying various (Q, h) pairs, illustrating the versatility and depth of the proposed theory and its contribution to the advancement of fixed point results in generalized metric environments.